The Relationship between Smoking Cessation and Health Insurance Coverage: An Analysis of Cost Saving and Health Outcomes - Al Farhan, Nasser (2023)
The use of tobacco products remains a significant public health concern worldwide, with smoking being a leading cause of preventable death and disease. Smoking cessation has been shown to improve health outcomes and reduce healthcare costs. However, the financial burden of smoking cessation can be a barrier for many individuals who lack adequate health insurance coverage. This has led to a growing interest in examining the relationship between smoking cessation and health insurance coverage, particularly in terms of cost savings and health outcomes. This study examines the relationship between smoking cessation and health insurance coverage, with a focus on analyzing the potential cost savings and health outcomes associated with quitting smoking. The current situation of health insurance coverage in the healthcare environment is discussed, highlighting the potential role of insurance in promoting healthy behaviors such as smoking cessation. Two methods of analysis were used: a theoretical analysis and an empirical analysis. The theoretical analysis involves a review of existing literature related to the topic, as well as an exploration of the potential cost savings that could be achieved through smoking cessation, including both direct and indirect costs, such as reduced healthcare costs and increased productivity. A second method employed in the study was an empirical analysis utilizing data from a large sample of individuals who had been patients in anti-smoking clinics across Saudi Arabia. This approach involved analyzing data on health insurance coverage and smoking behavior to estimate the potential impact of smoking cessation on health outcomes and costs. The results of the analysis indicated that smoking cessation has the potential to result in significant cost savings, with a ratio of nearly 1.5, while also leading to improved health outcomes. The study concludes by emphasizing the importance of health insurance coverage in promoting healthy behaviors such as smoking cessation, and the potential cost savings associated with such behavior change. The findings have important implications for policymakers and health insurers in promoting healthy behaviors and increasing access to smoking cessation programs that could have significant benefits for both individuals and society.